LAYANAN BIMBINGAN KELOMPOK MELALUI TEKNIK REINFORCEMENT UNTUK KEPERCAYAAN DIRI RENDAH SISWA KELAS VIII MTS DARUSSALAM - Laila Hanifa; Siti Fatimah; Tuti Alawiyah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
This study aims to describe group guidance services through the Reinforcement technique for students who have low self-confidence at Mts Darussalam. The research design used is descriptive qualitative research method. The subjects in the study were 4 students of class VIII at MTs Darussalam. Information assortment methods used are interviews, documentation and observation. The data analysis used is data collection, data reduction, presentation and conclusion drawing of data. The results of the research obtained from the research are group guidance services through the Reinforcement technique carried out to students who are indicated to have low self-confidence, student responses are very good to group guidance services through reinforcement technique. Obstacles faced by BK teachers when implementing services are inadequate facilities and infrastructure. Students experienced an increase in self-confidence after being given the Reinforcement technique group guidance service. Based on these results, group guidance services using the Reinforcement technique can be used as a reference for future researchers who will conduct research on the level of student confidence.Keywords:Self Confidence, Group Guidance Service, Reinforcement